Efficacy testing of an immersion vaccine against Aeromonas salmonicida and immunocompetence in ballan wrasse (Labrus bergylta, Ascanius) - Papadopoulou, Athina; Monaghan, Sean J; Bagwell, Nicola; Alves, Mickael Teixeira; Verner-Jeffreys, David; Wallis, Tim; Davie, Andrew; Adams, Alexandra; Migaud, Herve (Fish & Shellfish Immunology, 2022)
The development of effective vaccines is a critical step towards the domestication of emerging fish species for aquaculture. However, traditional vaccine delivery through intraperitoneal (i.p.) injection requires fish to reach a minimum size and age and therefore cannot provide protection at early developmental stages when infection may occur. This study investigated the effectiveness of immersion vaccination with respect to immunocompetence in a cleaner fish species (ballan wrasse, Labrus bergylta, Ascanius) used in Atlantic salmon farming as an alternative means to control sea lice. The species is susceptible to atypical strains of Aeromonas salmonicida (aAs) at early life stages (80 dph, MHC II and IgM transcripts were first reported at 35 and 75 dph, respectively, suggesting a window of immunocompetence. The results provide important new information on the onset of adaptive immunity in ballan wrasse and highlight that immersion vaccination in the species for protection against aAs should be performed at later developmental stages (>1.5 g) in the hatchery.